(untitled) (Global Journal of Management and Business Research, 2022)
The SANDHIGH field is one of the fields owned by PT Pertamina EP in West Java This field was discovered in 1987 and is a gas-producing field with peak production reaching 45-50 mmscfd in 2002-2003 and cumulative gas production up to December 2020 reaching 200 1 BSCF Gas production from this field has decreased drastically after 2003 until March 2022 the production is only under one mmscfd an apprehensive condition Problem analysis has been carried out using the Kepner-Tregoe method The leading potential cause of the decline in production in this field is the absence of a Plan of Development POD So exploitation activities that aim to increase production cannot be carried out or even restrain the decline rate in production In mid-2021 an initiation was made to make the SANDHIGH field POD by involving the Subject Matter Expert SME from the subsurface and surface engineers and advisors Discussions with SKK Migas as government representatives were also carried out intensively to produce the best development scenario based on Value Focus Thinking VFT From these discussions emerged three alternative development scenarios The Analytical Hierarchy Process AHP method is used to help select the best scenario from the three available options The assessment criteria used include capital expenditure operation expenditure expected profit implementation time operability and safety Based on the results of the AHP analysis it was found that Scenario-C was the best choice with a value reaching 54 4 This scenario consists of 2 infill well drilling two steps out well drilling and only producing gas until 2033